2012
DOI: 10.1123/jsm.26.2.127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of World Cup 2002 on the Bilateral Relationship Between South Korea and Japan

Abstract: The purpose of this study was to provide an analysis of an international sporting event as a possible catalyst for social change. Because of the unique circumstances surrounding the bid process, the dual hosting of the World Cup 2002 by Korea and Japan was seen as a unique opportunity to examine the power of sport as a catalyst behind change. Longitudinal secondary data were consulted to look at the economic, social and cultural impact of the event, while interviews with respondents in both nations gave more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Alternatively, governments should seek other instruments, perhaps with a national rather than international flavor, that could increase both national identity and social capital at a much lower economic cost. Heere et al (2012) suggested that in 2002, the relationship between Japan and South Korea did not improve because of the cohosting of the World Cup 2002, but because of the success of the Korean football team. In that particular situation, it appeared that a successful performance of a sport team was a much stronger catalyst for social change than the organization of an event.…”
Section: Resultsmentioning
confidence: 96%
“…Alternatively, governments should seek other instruments, perhaps with a national rather than international flavor, that could increase both national identity and social capital at a much lower economic cost. Heere et al (2012) suggested that in 2002, the relationship between Japan and South Korea did not improve because of the cohosting of the World Cup 2002, but because of the success of the Korean football team. In that particular situation, it appeared that a successful performance of a sport team was a much stronger catalyst for social change than the organization of an event.…”
Section: Resultsmentioning
confidence: 96%
“…Hosting the 2002 FIFA World Cup did however serve as a springboard, helping to increase tourism, trade and political dialogue, especially with South Korea (Horne & Manzenreiter, 2004). In addition, changes occurred in the perception of foreign nationals, notably amongst the youth population of Japan (Heere et al, 2012). Much has changed in the intervening period with respect to hosting SMEs, the contemporary competition for which has arguably peaked, at least outside the BRICS economies (Rookwood, 2019).…”
Section: Public Diplomacy Nation Branding and Sport In Japanmentioning
confidence: 99%
“…Governing bodies such as FIFA and the International Olympic Committee (IOC) often deny the crossover of sport, economics and politics, whilst otherwise emphasising situations in which sport is perceived to positively contribute towards improvements in financial growth and international relations, for instance (Heere et al, 2012). Differing governmental policies regarding sporting events in response to COVID-19 have demonstrated the prevalence of these connections.…”
Section: Introductionmentioning
confidence: 99%
“…A partir das obras levantadas em nossa revisão analítica da literatura, foi possível identificar quatorze fontes de referência (BLACK, PEACOK, 2013;GRIX, 2018 COMISSION, 2018;GRASSROOTS...,2018a;HAUT et al, 2018;HEERE et al, 2012;MURRAY, 2013;NYGÅRD, GATES, 2013;ÖZSARI et al, 2018 Para verificar a relevância dos instrumentos de diplomacia esportiva, a lista de indicadores foi submetida aos cinco peritos, sendo os mesmos: ex-comandante do Centro de Capacitação Física do Exército; três (03) oficiais QEMA, graduados no curso de instrutor de Educação Física da Escola de Educação Física do Exército e representantes do Brasil no CISM; e o presidente do CISM da Guiana Inglesa. Na Figura 2 pode-se observar a média das notas e o desvio padrão de cada ferramenta, tanto para a avaliação de sua importância no contexto esportivo militar quanto para o potencial de impacto.…”
Section: Identificação Das Ferramentasunclassified